An innovation of Agricultural Extension “Poloyode” As a Method of a Transactional Extension In Communication Of Local Cultural Based in Gorontalo Regency*) - Wawan K.Tolinggi; Lillyan Hadjaratie (Jurnal Komunikasi Pembangunan, 2014)
An agricultural extension activity is one of methods for changing knowledge, attitudes and behavior of farmers.Therefore, the adoption of technology and sharing of knowledge between farmers and extension workers can occur in transactional basis. The objectives of this paper are 1) to identify the innovation of extension Poloyode and, 2) to determine the communication approach in Poloyode innovation in Gorontalo regency. Findings of this paper show that: 1) Innovation of Poloyode extension is an innovation in agricultural extension that based on the local culture of Gorontalo regency. Innovation of Poloyode extension has 5 main outreach activities on assisting farmers sourced from indigenous philosophy of Gorontalo such as  Tuwoto, Mongembito, Maduma, Doluhupa and Molinepo; 2) innovation of Poloyode extension is only implemented internally by BP4K and BP3K , not to involve other stakeholders in agriculture.Keywords: Innovation Transactional Counseling, Poloyode, local culture, Gorontalo